2015
DOI: 10.1152/japplphysiol.00722.2014
|View full text |Cite
|
Sign up to set email alerts
|

Aging impairs heat loss, but when does it matter?

Abstract: Aging is associated with an attenuated physiological ability to dissipate heat. However, it remains unclear if age-related impairments in heat dissipation only occur above a certain level of heat stress and whether this response is altered by aerobic fitness. Therefore, we examined changes in whole body evaporative heat loss (HE) as determined using whole body direct calorimetry in young (n = 10; 21 ± 1 yr), untrained middle-aged (n = 10; 48 ± 5 yr), and older (n = 10; 65 ± 3 yr) males matched for body surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 43 publications
4
99
1
1
Order By: Relevance
“…In fact, our findings are consistent with their results such that we only found a difference in WBHL between our groups with the lowest (<20%) and highest (>30%) body fat percentage. In addition, while Stapleton et al (2015) reported greater fitness to dampen the age-related decrease in WBHL, these differences generally were observed at a rate of metabolic heat production exceeding that used in the present study (i.e., ≥400 W). Therefore, while aging appears to be the major predictor of WBHL in otherwise healthy adults, the impact of body fat and cardiorespiratory fitness cannot be entirely discounted.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In fact, our findings are consistent with their results such that we only found a difference in WBHL between our groups with the lowest (<20%) and highest (>30%) body fat percentage. In addition, while Stapleton et al (2015) reported greater fitness to dampen the age-related decrease in WBHL, these differences generally were observed at a rate of metabolic heat production exceeding that used in the present study (i.e., ≥400 W). Therefore, while aging appears to be the major predictor of WBHL in otherwise healthy adults, the impact of body fat and cardiorespiratory fitness cannot be entirely discounted.…”
Section: Discussioncontrasting
confidence: 56%
“…To date, research has demonstrated several factors -primarily age, cardiorespiratory fitness, and body fat -to influence wholebody heat loss (WBHL) and therefore alter susceptibility to heat stress in otherwise healthy adults (Larose et al 2013b;Stapleton et al 2015;Dervis et al 2016). Specifically, recent reports depict impairments in WBHL in physically active adults as young as 40 years of age (Larose et al 2013a(Larose et al , 2013b, although these studies isolated aging from other factors (i.e., participants were matched for body morphology and fitness).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicated that the age-related decline in aerobic fitness was associated with the decreased whole-body evaporative heat loss during exercise in the heat [100]. Moreover, a group of trained middleaged males (~48 years) exhibited greater whole-body heat loss than an untrained group during exercise [100].…”
Section: Effects Of Exercise Training On Thermoregulation In Diabeticmentioning
confidence: 99%
“…Indeed, while all age groups in this study stored almost double the amount of heat when ambient humidity was increased from dry (ϳ20%) to moderately humid (60%), the middle-aged and older adults still demonstrated disproportionately greater heat storage (by ϳ38%). In addition, these differences are dependent upon metabolic heat load (i.e., intensity of physical activity or work) such that marked reductions in the physiological capacity to dissipate heat were observed at a metabolic heat load ≥400 W and ≥325 W for older males and females, respectively (Stapleton et al 2015a(Stapleton et al , 2015b. The authors also noted that the age-related impairments were influenced by fitness such that middle-aged adults with high fitness showed high heat loss (i.e., compared with their younger counterparts), while middle-aged adults with low fitness showed low heat loss (i.e., compared with their older counterparts) (Stapleton et al 2015a(Stapleton et al , 2015b.…”
Section: Work In Hot Environmentsmentioning
confidence: 99%